T Pengaruh Efek Samping Obat Terhadap Kepatuhan Penggunaan Obat Pada Pasien Penyakit Jantung Koroner Di Rsud Brigjend H.Hasan Basry Hulu Sungai Selatan: Pengaruh Efek Samping Obat Terhadap Kepatuhan Penggunaan Obat Pada Pasien Penyakit Jantung Koroner Di RSUD Brigjend H.Hasan Basry Hulu Sungai Selatan - Nur Lathifah; Iwan Yuwindry; Muhammad Zulfadhilah (LPPM Universitas Sari Mulia, 2022)
Background: Coronary heart disease (CHD) is a condition caused by blockages in the arteries of the heart. CHD is the most common cause of cardiovascular disease worldwide, 45% of 9.4 million deaths are caused by CHD. CHD cases in Indonesia reached 1.2 million cases and increased to 2.7 million people who experienced CHD. The presence of CHD drug side effects and discontinuation of drug therapy is one of the risk factors for treatment failure Objective: Analyzing the effect of drug side effects on adherence to drug use in CHD patients at Brigjend H. Hasan Basry Hospital Hulu Sungai Selatan. Methods: This type of quantitative research uses an analytical observational design with a Cross Sectional design and the type of Purposive Consecutive Sampling. The sampling period was 4 weeks with a sample of 50 respondents with CHD. Data analysis used univariate and bivariate analysis with Spearman Rho test. The research instrument used the Naranjo questionnaire for drug side effects and MMAS-8 for adherence. Results: The results of this study indicate that there is a correlation between the variables of CHD drug side effects and drug use compliance which shows an effect with a significance value of 0.001 and a correlation coefficient of 0.470 which has a positive correlation direction with moderate strength of the relationship. Conclusion: there is a significant effect between the effects of side effects of CHD drugs on adherence to drug use in CHD patients at Brigjend H. Hasan Basry Hospital Hulu Sungai Selatan.